2005
DOI: 10.1111/j.1442-9071.2005.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase 677 C‐T and homocysteine levels in Turkish patients with pseudoexfoliation

Abstract: In Turkish patients with PEX, the authors could not find any association between Hcy levels, MTHFR 677 C-T polymorphism, and the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
4
19
1
1
Order By: Relevance
“…The frequency of TT genotype in younger NTG patients in our study (38.9%) is much higher when it is compared with the results reported in different ethnic populations (2-17.9%). 10,13,14,16,[22][23][24][25][26][27][28][29] Genetic traits of a disease should be more important in younger patients than in older ones. If one has a genetic predisposition to a disease, it is likely that the disease should develop earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of TT genotype in younger NTG patients in our study (38.9%) is much higher when it is compared with the results reported in different ethnic populations (2-17.9%). 10,13,14,16,[22][23][24][25][26][27][28][29] Genetic traits of a disease should be more important in younger patients than in older ones. If one has a genetic predisposition to a disease, it is likely that the disease should develop earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches on the association of 677C4T MTHFR gene polymorphism and hyperhomocysteinaemia with high-tension POAG and pseudoexfoliation glaucoma revealed conflicting results and the association is not obvious. [25][26][27][28] As the barotrauma from high IOP is the primary pathogenesis of optic nerve damage in hightension POAG, there appears to be low possibility of the association between hyperhomocysteinaemia and hightension POAG.…”
mentioning
confidence: 99%
“…The role of Hcy has been investigated in context with PEXG and POAG; most studies on PEXG have found an association with Hcy [16-19, 23, 25-27] despite some conflicting reports present in the literature [28], while only a few studies have confirmed the association in POAG patients [9,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Five separate studies published during the last two years show HH as a risk factor for exfoliation syndrome (XFS) and exfoliative glaucoma (XFG) [1,3,22,33,49]. On the other hand, in a Turkish study no correlation was found in occurrence of HH between XFS and control subjects [45].…”
Section: Introductionmentioning
confidence: 95%